## Differential Operators

We're doing differential operators in my Differential Equations class right now, and our professor assigned the following problem to us:

(D-x)(D+x)

Which inevitably gives us the following terms as part of the final answer: Dx-xD

The answer in the book tells me that Dx-xD = 1, and some preliminary research has told me that this is true. What I couldn't find was the why. Why, or how, does Dx-xD result in 1? And does -Dx+xD = -1?
 PhysOrg.com science news on PhysOrg.com >> Ants and carnivorous plants conspire for mutualistic feeding>> Forecast for Titan: Wild weather could be ahead>> Researchers stitch defects into the world's thinnest semiconductor

Recognitions:
Homework Help
 Quote by tirnanog84 We're doing differential operators in my Differential Equations class right now, and our professor assigned the following problem to us: (D-x)(D+x) Which inevitably gives us the following terms as part of the final answer: Dx-xD The answer in the book tells me that Dx-xD = 1, and some preliminary research has told me that this is true. What I couldn't find was the why. Why, or how, does Dx-xD result in 1? And does -Dx+xD = -1?
product rule gives
Dx=1+xD
might be easier to see with a function
D(xy)=(Dx)y+x(Dy)=y+x(Dy)=(1+xD)y
so
Dx=1+xD
 That is because $$\frac{d}{dx}\left(xf(x)\right)-x\frac{d}{dx}\left(f(x)\right)=xf'(x)+f(x)-xf'(x)=f(x)$$ $$(Dx-xD)f(x)=f(x)$$ Hence Dx-xD=1

Thanks!